External debt sustainability : guidelines for low- and middle- income countries - Loser, Claudio M. (UN New YorkUS, 2004)
Looks at the sources of debt vulnerability, including internal and external shocks. Covers issues of debt control, currency and maturity structure of debt and its management, risk management of debt and restructuring issues. Deals with external debt vulnerability and risk indicators, including external, domestic, and market indicators.